2016
DOI: 10.1142/s175882511650068x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Characterization of the Dynamic Properties of Flax Fiber Reinforced Composites

Abstract: In this paper, the damping properties of flax fiber reinforced composites were investigated. Throughout a series of resonance vibration tests, the natural frequencies and the modal damping were evaluated. A numerical modelling was also produced by using a finite element model to determine the energies dissipated in each layer of the laminate structure in order to calculate the damping factors. The results obtained for the dynamic properties of flax fiber reinforced composites from experimental data and numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The vibration damping was estimated using a half-power bandwidth method, also known as peak picking, from measured frequency response functions (FRFs) [51]. A similar procedure was also used in [16,19,22] to characterise the damping of flax fibre reinforced composites.…”
Section: Vibration Damping Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibration damping was estimated using a half-power bandwidth method, also known as peak picking, from measured frequency response functions (FRFs) [51]. A similar procedure was also used in [16,19,22] to characterise the damping of flax fibre reinforced composites.…”
Section: Vibration Damping Measurementmentioning
confidence: 99%
“…Prabhakaran et al, not only showed the superior vibration damping properties of flax fibres when compared with glass fibre composites, but also demonstrated higher sound absorption coefficients both at high (2000 Hz) and low (100 Hz) frequencies [18]. Daoud et al investigated the damping properties of flax fibre reinforced composites via resonance vibration tests and produced numerical model to predict the damping factors investigating the effect of the fibre orientations and of a thin viscoelastic interleaf [19,20]. Rahman et al showed a strong dependence in natural frequencies and loss factors from fibre orientation and content in a flax fibre reinforced polypropylene matrix [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This analyser associated with a computer (PC) set the acquisition conditions and then did the analysis of the signals acquired. Frequency response analyses were carried out to obtain the natural frequencies using the fre-H. Daoud [7], Daoud et al [6] and Hammami et al [8]. Using this method the loss factor η_n was calculated by equation 1.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, experimental analyses were carried out to investigate the damping factor of composites with flax fibre to determine the frequency responses and the damping properties of the structure. These experiments were carried out using the same procedure used by Daoud et al [6]. The results obtained showed that natural fibres have promising effects on damping vibration.…”
Section: Introductionmentioning
confidence: 97%
“…Another advantage of natural fibers over carbon and glass fibers is their better damping properties [Daoud et al, 2016]. Damping alleviates the relative motions in an object and converts kinetic energy into heat or other disposable energy types.…”
Section: Sound and Vibration Damping Aspects Of Plant Fiber Compositesmentioning
confidence: 99%